Mine the gap: Bitcoin and the maintenance of trustlessness - Vidan, G; Lehdonvirta, V (SAGE Publications, 2018)
Subscribing to a techno-utopian discourse replacing institutions and experts with “trust in code,” digital alternative currency Bitcoin is pitched as a “math-based money” governed by incorruptible code rather than human regulators. In three cases, which occurred between 2013 and 2015, we examine this system at moments of breakdown. In contrast to the discourse, we find that power is concentrated to critical sites and individuals who manage the system through ad hoc negotiations, and who users must therefore implicitly trust—a contrast we call Bitcoin’s “promissory gap.” But even in the face of such contradictions between premise and reality, the discourse is maintained. We identify four authorizing strategies used in this work: conflating people with devices, assuming actors conform to notions of economic rationality, appealing to technical expertise, and explaining contradictions as temporary bugs. We contend that these strategies are mobilized widely to legitimize a variety of applications of algorithmic regulation and peer production projects.